Abnormal physiological responses toward sensory stimulus are related to the attention deficits in children with sluggish cognitive tempo - Yung, Trevor W. K.; Lai, Cynthia Y. Y.; Chan, Chetwyn C. H. (Frontiers in Neuroscience, 2022)
Previous studies have found that sluggish cognitive tempo (SCT) is often associated with difficulties in real life functioning such as social problem, emotional difficulties and academic learning difficulties. However, the underlying mechanism contributing to the SCT symptoms and its associated real-life difficulties have still not been clearly understood. Previous study has found that SCT symptoms were associated with hypo-arousal and hyper-arousal towards sensory stimulus. However, it is still unclear whether such abnormal arousal regulation is related to the sustained attention difficulties which have been found to be related to social difficulties and withdrawn behaviour in children with SCT. In the current study, arousal regulation deficit in SCT is examined by the physiological responses quantified by HRV and EEG in sensory challenge paradigm. The aim of the present study is to establish a linkage between arousal regulation reflected by HRV and EEG and attention difficulties in children with SCT. The results of the current study showed that higher theta power in auditory stimulation condition than in resting condition was associated with higher omission errors in sustained attention task. It was found that higher parasympathetic activities during sensory stimulation condition was associated with higher commission errors. These results reflected that hyper-sensitivity towards stressful sensitivity towards stressful sensory stimulus is associated with attention difficulties in children with SCT. This further supported the notion that SCT should be conceptualized as a condition characterized by multiple deficits in different biological systems such as cognitive system, negative valence system and arousal regulatory system.